Minimizing psychological impact on workers in genuine redundancy: formulating guidelines for employer - Ali Mohamed, Ashgar Ali; Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan; Kasi, Arun (International Organization Center of Academic Research, 2018)
The competing interests of a worker and an employer require that a worker’s security of tenure must be balanced against the just expectation of the employer for latitude, under genuine redundancy in the organisation, to retrench the surplus labour or workers. Such redundancy may arise due, among others, to a reduction of business activities, perceived advantages of greater mechanisation and technological change, deployment of capital resources in different ways, reorganisation of business operations with a view to enhancing profitability, and reducing losses either generally or in selected areas. For a retrenchment to be justified, there must be convincing grounds to establish redundancy. Whether a genuine redundancy is established and a retrenchment is justified in any particular case would depend on the factual matrix and circumstances of each case. It is not doubted that a retrenchment of workers would have psychological impact on the affected workers, more so if the worker has been in service for a long time in the organisation. He will likely face difficulty in relocating and/or securing other employment due to various factors. Hence, it is appropriate that certain viable and practicable guidelines are developed for the employer to adhere to in order to minimize the impact of retrenchment exercise on the workers. It is an established rule that an employer should ensure that retrenchment, if necessary, is carried out in a fair manner. It includes manner of selecting the worker or workers declared to be redundant, giving a fair opportunity to them to make representations on the possibility of re-deployment, etc. The courts would not normally interfere with a bona fide exercise of rights of an employer in a retrenchment exercise, which rights are inherent in it. However, any form of victimisation of the employee, whether by arbitrary, perverse, baseless action or otherwise by the employer which is considered to be unnecessarily harsh or was not just or fair, or other mala fide action on the part of the employer, may warrant the courts’ interference. In light of the above, this paper will discuss retrenchment and its psychological impact on workers with particular focus on formulating some guidelines for employers with a view of minimising the impact.